2016
DOI: 10.15252/emmm.201606798
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of clinical metabolic profiling studies in cancer: challenges and opportunities

Abstract: Cancer cell metabolism has received increasing attention. Despite a boost in the application of clinical metabolic profiling (CMP) in cancer patients, a meta‐analysis has not been performed. The primary goal of this study was to assess whether public accessibility of metabolomics data and identification and reporting of metabolites were sufficient to assess which metabolites were consistently altered in cancer patients. We therefore retrospectively curated data from CMP studies in cancer patients published dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 37 publications
5
75
1
Order By: Relevance
“…19, 49-51), tumor metabolomic analyses have given diverse results. Meta-analyses have identified a general trend for most proteogenic amino acids to be increased in tumors (52). In our own studies of pancreas cancer, however, we found a more interesting pattern, with increased concentrations of amino acids used purely for protein synthesis, but lower concentrations of those used also as nucleotide precursors, with glutamine being the most depleted metabolite (53).…”
Section: Metabolite Concentration Changes In Tumorsmentioning
confidence: 47%
“…19, 49-51), tumor metabolomic analyses have given diverse results. Meta-analyses have identified a general trend for most proteogenic amino acids to be increased in tumors (52). In our own studies of pancreas cancer, however, we found a more interesting pattern, with increased concentrations of amino acids used purely for protein synthesis, but lower concentrations of those used also as nucleotide precursors, with glutamine being the most depleted metabolite (53).…”
Section: Metabolite Concentration Changes In Tumorsmentioning
confidence: 47%
“…By providing external oxidizing power, extracellular pyruvate could conceivably release the potential block in proliferation and tumor growth linked to defective aspartate biosynthesis due to the lack of NAD + recycling (Sullivan et al, 2015(Sullivan et al, , 2018Birsoy et al, 2015;Garcia-Bermudez et al, 2018). Pyruvate was suggested to be increased in malignant compared with normal tissues (Goveia et al, 2016). We thus analyzed pyruvate in tissue excised from the site of grafted 4T1r 0 cells at time points used to establish the lines, in parental and D5-D25 cells (cf.…”
Section: Pyruvate May Not Be Limiting For Tumor Growthmentioning
confidence: 99%
“…It was recently shown that in cancer cells, mitochondria can use lactate in a manner that is distinct from how it is used in the cytoplasm (i.e., as fuel to provide nutrients to cells), implicating a pivotal role in carcinogenesis. A metanalysis of curated data from clinical metabolic profiling studies in cancer patients confirmed well‐known increases in glycolytic metabolites and also unveiled unprecedented changes in other metabolites such as ketone bodies and amino acids (such as histidine and tryptophan) . Another extensive computational analysis of metabolomics data from 900 tissue samples covering >900 metabolites revealed several polyamines and kynurenines being associated with several aggressive tumor types …”
Section: Opportunities Beyond Warburg's Effect Glycolysis Lactate Mmentioning
confidence: 79%